Peningkatan Hasil Belajar IPA Siswa Kelas V MIN 2 Agam melalui Model Pembelajaran Inkuiri Terpimpin - Supia Wati, Mira; Mulyana, Sri (Journal of Development Education and Learning (JODEL), 2025)
This Classroom Action Research investigates the effectiveness of the guided inquiry model in improving science learning outcomes among fifth-grade students in an Indonesian elementary school. The study was conducted with 28 students at MIN 2 Agam District, during the second semester of the 2024/2025 academic year. The intervention was carried out in two cycles, each consisting of three lessons, following the stages of planning, implementation, observation, and reflection. Data were collected through cognitive tests (20 multiple-choice items: pretest, posttest Cycle I, posttest Cycle II), science process skills observation sheets (4-point rubric), teacher journals, and student response questionnaires (4-point Likert scale). Descriptive quantitative analysis was used to examine changes in mean scores and achievement percentages, while qualitative analysis explored patterns emerging from journals and questionnaires. Findings revealed that the guided inquiry model consistently improved students’ mean scores from 54.6 (pretest) to 70.3 (posttest Cycle I) and 86.1 (posttest Cycle II), with the proportion of students achieving the target increasing from 28.6% to 89.3%. Science process skills and learning motivation also demonstrated notable development. The study concludes that guided inquiry, supported by structured worksheets, teacher scaffolding, and heterogeneous group organization, effectively enhances students’ conceptual understanding, scientific process skills, and motivation in science learning at the elementary level. For publication purposes, the inclusion of raw data, inferential statistical tests, and instrument reliability reporting is recommended to strengthen the evidence.